แบบเรื่องและอนุภาคสัตว์สีเผือกในตำนานเมืองล่มภาคอีสาน; Tale Type and White Animal’s Motifs In Ruined City Legends of North Eastern Regio - ลากุล, อนันต์; ตุลารักษ์, อุมารินทร์ (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2018)
การศึกษาครั้งนี้มีวัตถุประสงค์ เพื่อศึกษาแบบเรื่องและอนุภาคสัตว์สีเผือกในตำนานเมืองล่มที่แปรสภาพเป็นบึงน้ำในภาคอีสาน โดยใช้กรอบแนวคิดแบบเรื่องและอนุภาคทางคติชนวิทยา ซึ่งปรากฏผล ดังนี้ จากการศึกษาพบว่า ตำนานเมืองล่มพบทั้งหมด 10 เรื่อง จาก 30 สำนวน จัดอนุภาคได้ 5 ประเภท คือ อนุภาคการกินปลาไหลเผือก อนุภาคการกินกระรอกเผือก อนุภาคการจับปลาดุกเผือก อนุภาคการกินเก้งเผือก และอนุภาคการกินปลาฝาเผือก โดยสาเหตุของเมืองล่มทั้งหมดนั้นเกิดจากการกระทำของสัตว์เผือกและเหล่านาค กล่าวได้ว่า สัตว์สีเผือกจึงมีลักษณะแทนสัญญะของ “นาค” และ “การทำลาย” อย่างไรก็ตาม ในตำนานเมืองพานนั้นได้ให้พังพอนเผือกแทนสัญญะของสัตว์ที่คอยคุ้มครองบ้านเมือง ซึ่งต่างจากตำนานเมืองล่มฉบับอื่น ดังนั้น นิยามของสัตว์สีเผือกในภาคอีสานจึงมีลักษณะแทนลางบอกเหตุหรือสิ่งผิดปกติ มีความหมายสองนัย กล่าวคือ สัตว์สีเผือกนัยยะของการทำลาย และสัตว์สีเผือกนัยยะของการคุ้มครอง อนึ่ง น่าสังเกตว่า ตำนานเหล่านี้มีการเล่าเรื่องกระจายอยู่ในพื้นที่ภาคอีสานตอนบนและตอนกลางเท่านั้น Abstract This purpose of this research was to study the legend of ruined city which was transformed to a lake in North Eastern region by using Tale Conceptual Model and Folklore’s Motifs as follows: The study found that it had 10 stories from 30 chapters, which are categorized into 5 motifs by the consumption of white eels, white squirrel, white catch fish, white muntjac, and white soft-shelled turtle. The main reason of ruined city is caused by power of the white animals which are considered as a representative of “Naga” and the wrath of Naga. It is remarkably noticed that white animals were representative of “Naga” and “Wrath" whereas Pan City legend was raised white mongoose to be the guardian of the city which is different from others. Therefore, the meaning of white animals in North Eastern region was the representative of bad omen, or unusual phenomenon consists of 2 significant meanings which can be both of the wrath and the guardian, and these legends have existed in North Eastern and Central Eastern only.